The Impact of Rice Intensification Three Times a Year (IP300) on Rice Field Degradation in West Lombok District - Yusuf, M; Fadli, Fadli; Rahayu, Muji (Jurnal Biologi Tropis, 2026)
The aim of this research are to: (1) Identify the main factors in the implementation of IP300 that contribute to the degradation of rice fields in West Lombok Regency; (2) Formulate a strategy for mitigating rice field degradation that supports increased productivity without sacrificing soil quality in the IP300 implementation area; and (3) Evaluate farmers' perceptions and responses to the impact of IP300 on soil fertility and sustainability of farming businesses. The method used is a descriptive method, while data collection uses survey techniques and literature studies. The results of the study indicate that: (1) The main factors of land degradation in the implementation of IP300 in West Lombok Regency are: intensification of chemical fertilizer use, intensive pesticide use, and planting systems and cultivation practices in IP300; (2) The strategy for mitigating rice field degradation that supports increased productivity without sacrificing soil quality in the IP300 implementation area is: restoration of soil function through balanced fertilization, adaptive irrigation, crop diversification, IPM, and adoption of precision technology; and (3) The perception and response of rice farmers to IP300 are starting to shift from simply pursuing productivity to awareness of sustainability. However, adaptive responses have only emerged in some farmer groups.